Kontruksi Realitas Motif Polisi Lalu-Lintas Kota Bandung - Asep Dion Nugraha (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2017)
The policeman performance frequently gets public criticism, but many people are interested in applying job as a police officer.Â There are particular motives in each person which leads him to choose a profession as a policeman. Because of the reasons and drive in human, the ones do something. This research uses a qualitative approach, that is, Constructing Reality of Bandung Traffic Policeman, by using a phenomenology study analysis. The results of the research are: expectancy and past experience motives; economic need motives; gallant motives, commanding and prestigious; family and environment motives; destiny, fortune, or fate motives; with typication: self-esteem fulfillment; interaction and self-actualization; achievement fulfillment; finally he becomes a wise or sensible (â€˜arif) person. Â